Intergenerational diabetes and obesity-A cycle to break? - Ronald C W Ma; Barry M Popkin (PLoS Medicine)
Ronald Ma and Barry Popkin discuss the urgent need and challenges to reduce intergenerational transmission of obesity and diabetes.